Effect of Incision Site on Pre-existing Astigmatism in Phacoemulsification - Muhammad Rafiq Afridi, Imran Ahmad, Akbar Khan, Mumtaz Alam (Pakistan Journal of Ophthalmology, 2018)
Purpose: The purpose of the study was to determine the mean change in pre-existing astigmatism, by site of incision in phacoemulsification. Material and Methods: It was a prospective study, conducted at Ophthalmology Department, Khyber Teaching Hospital Peshawar, from March 1st 2012 to August 31st 2012. All cases were operated by phacoemulsification with intraocular lens implantation keeping 3.2 mm incision perpendicular to steep meridian of cornea. Astigmatism was measured in diopters by keratometry pre-operatively and at 6 weeks post-operatively. Results: Total number of patients included in the study was 113. The mean pre-operative astigmatism was 1.90 ± 0.49 diopters with a range from 1.20 to 3.25 diopters. The astigmatism decreased in 105 eyes (92.92%), remained unchanged in 4 eyes (3.53%) and increased in 4 eyes (3.53%). The mean reduction in astigmatism at the end of study was 0.54 ± 0.27 diopters. This difference in preoperative and postoperative was statistically significant (P value = 0.0001). Conclusion: A 3.2 mm Perpendicular incision at the steep meridian of cornea is effective in reducing the pre-existing astigmatism.